Organizational culture and company values: a cross-sectional study on public companies in Indonesia - Andreas Andreas; Tatang Ary Gumanti (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose – This study examined the effect of corporate culture (the availability of corporate pages on the website of the company) on the corporate value (Tobin’s Q) of the companies listed on the Indonesia Stock Exchange. Design/methodology/approach – The study uses secondary data extracted both from the company website and the financial reports for the year 2019. There are 530 companies that met the selection criteria. The hypothesis is tested using the cross-sectional ordinary least square (OLS) regression. Findings – The results show a modest positive effect of corporate culture on corporate value. The robustness test reveals that the finding is more pronounced among small companies. The study also includes four other variables, namely employee activities, employee training programs, honors earned, and charity programs. It was found that only honors earned have a significant positive effect on corporate value. Research limitations/implications – This study uses a cross-sectional-based analysis, making it lack of capability to look for the multi-years effect of the variables being investigated. It measures Tobin’s Q using the end of the fiscal year stock price. Using one single day as the base of calculation may ignore the fluctuation of the stock prices over the whole year. Practical implications – Given the findings, it is recommended that the company shall disclose and promote its corporate culture as a means of informing potential investors about the company’s strong commitment to doing business with a specific culture. Originality/value – The study examines the issue using cross-sectional data and divides the sample based on the size of the companies allowing it to seek more evidence on whether the main issue under investigation is sensitive to the size of the company.